Enhancing Patient Experience in Office-Based Laryngology Procedures With Passive Virtual Reality. Issue 1 (January 2021) - Chang, Joseph; Ninan, Sen; Liu, Katherine; Iloreta, Alfred Marc; Kirke, Diana; Courey, Mark
Objectives: Virtual reality (VR) has been used as nonpharmacologic anxiolysis benefiting patients undergoing office-based procedures. There is little research on VR use in laryngology. This study aims to determine the efficacy of VR as anxiolysis for patients undergoing in-office laryngotracheal procedures. Study Design: Randomized controlled trial. Setting: Tertiary care center. Methods: Adult patients undergoing office-based larynx and trachea injections, biopsy, or laser ablation were recruited and randomized to receive standard care with local anesthesia only or local anesthesia with adjunctive VR. Primary end point was procedural anxiety measured by the Subjective Units of Distress Scale (SUDS). Subjective pain, measured using a visual analog scale, satisfaction scores, and procedure time, and baseline anxiety, measured using the Hospital Anxiety and Depression Scale (HADS), were also collected. Results: Eight patients were randomized to the control group and 8 to the VR group. SUDS scores were lower in the VR group than in the control group with mean values of 26.25 and 53.13, respectively ( P = .037). Baseline HADS scores did not differ between groups. There were no statistically significant differences in pain, satisfaction, or procedure time. Average satisfaction scores in VR and control groups were 6.44 and 6.25, respectively ( P = .770). Average pain scores were 3.53 and 2.64, respectively ( P = .434). Conclusion: This pilot study suggests that VR distraction may be used as an adjunctive measure to decrease patient anxiety during office-based laryngology procedures. Procedures performed using standard local anesthesia resulted in low pain scores and high satisfaction scores even without adjunctive VR analgesia. Level of Evidence: 1